2014
DOI: 10.1002/alr.21406
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life improvement from sinus surgery in chronic rhinosinusitis patients with asthma and nasal polyps

Abstract: CRS patients with both asthma and nasal polyps or asthma alone experience a larger QOL benefit from FESS immediately after FESS compared to CRS patients without asthma or polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 25 publications
1
41
1
Order By: Relevance
“…The same authors recently followed a cohort of CRSwNP patients after ESS and found an improvement in asthma symptoms score, daily peak expiratory flow, and nasal inspiratory flow. 867 Zhang et al 868 observed in their retrospective analysis that patients with both NP and asthma experience a larger QoL improvement measured by SNOT-22 at 1 and 3 months, when compared to patients without asthma or NPs. In a smaller series of patients with NP, ESS did not affect the asthma state.…”
Section: Viiib Crswnp: Comorbid Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors recently followed a cohort of CRSwNP patients after ESS and found an improvement in asthma symptoms score, daily peak expiratory flow, and nasal inspiratory flow. 867 Zhang et al 868 observed in their retrospective analysis that patients with both NP and asthma experience a larger QoL improvement measured by SNOT-22 at 1 and 3 months, when compared to patients without asthma or NPs. In a smaller series of patients with NP, ESS did not affect the asthma state.…”
Section: Viiib Crswnp: Comorbid Asthmamentioning
confidence: 99%
“…69,75,1347 Patients with CRSwNP tend to have better baseline QoL relative to patients with CRSsNP; however, specific symptoms such as nasal airway obstruction and olfactory disturbance tend to dominate CRSwNP. 75,77,868,1347,1348 Interestingly, patients with CRSwNP have the greatest improvement in QoL following ESS despite their relatively better baseline QoL. 75,77 …”
Section: Ess Outcomes Differences Between Crswnp and Crssnpmentioning
confidence: 99%
“…Ample evidence in the literature supports ESS, because overall quality of life is better, endoscopic scores are improved, and patients' symptoms are better controlled. 24,27,[33][34][35] An improvement in sinonasal symptoms, such as thick nasal discharge and nasal obstruction, can reasonably be achieved with appropriate surgery and postoperative care. 35 However, the return of olfaction is difficult to predict.…”
Section: Impact Of Endoscopic Sinus Surgery On Olfaction In Chronic Rmentioning
confidence: 99%
“…46 Longitudinal SNOT-22 data has similarly been reported across a variety of disease processes (e.g., CRS, anterior skull base neoplasms, cystic fibrosis associated sinusitis); 711 however, the majority of these studies are retrospective in nature and derived from a single-institution experience. One notable exception is the English and Welsh cohort, which has investigated five year follow-up SNOT-22 scores undergoing ESS with and without nasal polyposis.…”
Section: Introductionmentioning
confidence: 99%